カンタンナ ブッタイ ニヨッテ デキル ユキ ノ フキダマリ ニ カンスル ケンキュウ - 真木, 太一; マキ, タイチ; MAKI, Taichi (国立極地研究所, 1975)
P(論文) The effect of obstacle arrangement on snowdrifts was experimentally studied at Syowa Station in Antarctica. Different patterns of snowdrift were obtained by changing the alignment of the obstacles. The author showed the distribution patterns of snowdrift in the case of a straight-line alignment of two flat boards and two different orthogonal arrangements of two flat boards, standing and lying cylinders, and a straight-line alignment of two rectangular prisms. The snowdrift was measured immediately after blizzards with maximum instantaneous wind velocity 31 to 36m/s, mean air temperature for the period of strong wind over 20m/s -6 to -10℃, maximum amplitude of wind direction 25 degrees and gustiness 1.1 to 1.3. The ridge of snowdrift in Antarctica was more distinct than that in Japan, because of the smaller gustiness and the less variation in the wind direction. The effect of the obstacles extended over the distance up to 20 to 30 times the obstacle height. This is similar to the effect of a wind break fence. departmental bulletin paper